Letter to the Reader - Reali, Aline Maria de Medeiros Rodrigues (Revista Eletrônica de Educação, 2015)
<!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–><span style="font-size: 11.0pt; line-height: 115%; font-family: ";Calibri";,";sans-serif";; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ";Times New Roman";; mso-bidi-theme-font: minor-bidi; mso-ansi-language: PT-BR; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">DOI: http://dx.doi.org/10.14244/198271991458 Letter to the reader v. 9, n. 3, 2015.